Cytometric comparisons between circulating tumor cells from prostate cancer patients and the prostate tumor derived LNCaP cell line - Lazar, Daniel C. (2012)
Many important experiments in cancer research are initiated with cell line data analysis due to the ease of accessibility and utilization. Recently, the ability to capture and characterize circulating tumor cells (CTCs) has become more prevalent in the research setting. This ability to detect, isolate, and analyze CTCs allows us to directly compare specific protein expression levels found in patient CTCs to cell lines. In this study, we use immunocytochemistry to compare the protein expression levels of total cytokeratin (CK) and androgen receptor (AR) in CTCs and cell lines from patients with prostate cancer to determine what translational insights might be gained through the use of cell line data. A non-enrichment CTC detection assay enables us to compare cytometric features and relative expression levels of CK and AR by indirect immunofluorescence from prostate cancer patients against the prostate cancer cell line LNCaP. We measured physical characteristics of these two groups and observed significant differences in cell size, fluorescence intensity, and nuclear to cytoplasmic (N/C) ratio. We hope that these experiments will initiate a foundation to allow cell line data to be compared against characteristics of primary cells from patients.